What maternal morbidities are and what they mean for women: A thematic analysis of twenty years of qualitative research in low and lower-middle income countries. - Isabelle L Lange; Atf Gherissi; Doris Chou; Lale Say; Veronique Filippi (PLoS ONE, 2019)
Background With an estimated 27 million annual incidents of maternal morbidity globally, how they are manifested or experienced is diverse and shaped by societal, cultural and personal influences. Using qualitative research to examine a woman's perception of her pregnancy, its complications, and potential long-term impact on her life can inform public health approaches and complement and inform biomedical classifications of maternal morbidities, historically considered a neglected dimension of safe motherhood. As part of the WHO's Maternal Morbidity Working Group's efforts to define and measure maternal morbidity, we carried out a thematic analysis of the qualitative literature published between 1998 and 2017 on how women experience maternal morbidity in low and lower-middle income countries. Results and conclusions Analysis of the 71 papers included in this study shows that women's status, their marital relationships, cultural attitudes towards fertility and social responses to infertility and pregnancy trauma are fundamental to determining how they will experience morbidity in the pregnancy and postpartum periods. We explore the physical, economic, psychological and social repercussions pregnancy can produce for women, and how resource disadvantage (systemic, financial and contextual) can exacerbate these problems. In addition to an analysis of ten themes that emerged across the different contexts, this paper presents which morbidities have received attention in different regions and the trends in researching morbidities over time. We observed an increase in qualitative research on this topic, generally undertaken through interviews and focus groups. Our analysis calls for the pursuit of high quality qualitative research that includes repeat interviews, participant observation and triangulation of sources to inform and fuel critical advocacy and programmatic work on maternal morbidities that addresses their prevention and management, as well as the underlying systemic problems for women's status in society.